(untitled) (Brazilian Journal of Police Sciences, 2023)
Personal prevention measures present a serious risk to citizens’ rights. In particular, the judgement of dangerousness, on which they are grounded, has a lack of determination both in the basis and in the yardstick, representing a critical point in the Italian discipline with regard to constitutional guarantees and the guarantees of the European Convention on Human Rights. In the development of a constitutional and conventional statute of prevention, it is necessary to avoid deriving, by analogy, a series of protections required in the criminal field, creating instead an autonomous range of guarantees, due to the specific structure of such measures, first of all the absence of an illegal act of the recipient as their prerequisite. It is therefore appropriate to abandon the attempt to reproduce, in this field, abstract symmetries with criminal law: it is too easy for the legislator to avoid the problem of a sanction without a crime through formal qualifications and the structure of prevention is too distant from the structure of an indictment, as conventional jurisprudence reminds us. Rather, it is better to update the habeas corpus features in order to be able to oppose the several abusive mechanisms used today to reduce personal freedom, sometimes before, sometimes regardless of the commission of a crime.